Penggunaan Bahasa dalam Bimbingan dan Konseling - Mujiyati, Mujiyati (STKIP Muhammadiyah Pringsewu, 2017)
Abstract: The language arising from interaction between individuals gives a meaning that the relationship of language and culture has its own influence for the habit of thinking and behaving individually. This is because language is a means of expressing the mind so that it reflects the individuals self-image of the behavior he is showing. Language is a means of thinking and communication for the individual, so communication skills can be defined as language skills. In the context of education, language is the medium of instruction, while in the realm of guidance and counseling, language is a reflection of the counselees mind by reflecting from his world view, so that by understanding the language, the counselor will understand the counselees perspective. Language is closely tied to individual feelings and activities or behaviors. In the context of guidance and counseling, the language used by counselors can be a weapon and should be used wisely. The language should be cohesive, coherent, accurate, and meaningful in the process of guidance and counseling services to enable effective communication between counselors and counselors. The direction of research that will be done more emphasis on the topic of language use by the counselor and the language response of the counselee as an effort to examine more in the use of language appropriate to the educational situation.Keywords: Language, Communication, Education, Guidance and Counseling